Análise do uso de resíduo de caulim intercalado com acetato de potássio em compósito de matriz polimérica - SANTOS, Jenniffer Cristina Pena dos (2024)
Due to the increase in industrial waste volume, new alternatives are being sought, such as reusing this material to produce new technologies through composite materials. This study aims to chemically modify kaolin residue for its application as a reinforcing mineral filler in polyester matrix composite production. The untreated and treated residues were characterized using X-ray diffraction and thermal analysis to verify their mineralogical composition, and pycnometry was performed to determine the specific mass of the treated residue. Subsequently, a stoichiometrically prepared solution of untreated residue, potassium acetate, and distilled water was agitated for 8 hours at room temperature. After 24 hours, the material was filtered and placed in an oven at 60 °C for 6 hours. The composite plates were fabricated using the hand lay-up method combined with compression, and the mass fractions used were 0% (Pure Resin – RP), 10% (Treated Kaolin Residue 10 – RCT-10), and 20% (Treated Kaolin Residue 20 – RCT-20). After testing, it was found that the incorporation of chemically treated mineral filler resulted in statistically significant changes in physical properties (water absorption, apparent porosity, and apparent specific mass) and imparted relevant characteristics such as flame propagation resistance, particularly for RCT-10. However, the tensile strength limit (TSL) results showed a slight decrease compared to pure resin. It can be said that the research achieved satisfactory results, as demonstrated in the literature, in addition to the considerable importance of waste reuse to help reduce environmental impacts.